Implementasi Sistem Informasi Desa (SID) Berbasis Web Terhadap Efisiensi Dan Transparansi Di Kantor Desa Tommo, Kabupaten Mamuju, Sulawesi Barat - Indri Winarti; Jumrah; Hari Yeni (CV. SINAR HOWUHOWU, 2026)
The development of information technology encourages village governments to continuously strive to improve the quality of public services through the utilization of information systems. One form of innovation developed is the web-based Village Information System (SID), which is designed to help village officials work more efficiently while increasing information transparency to the public. This study aims to examine the implementation of the web-based SID in supporting service efficiency and transparency at the Tommo Village Office, Mamuju Regency, West Sulawesi. The study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation studies. The results show that the implementation of the web-based SID can accelerate village administration processes, improve data accuracy, and facilitate public access to information. However, its implementation still faces obstacles, particularly related to limited human resources and technological infrastructure support. Therefore, ongoing training efforts and strengthening of facilities and infrastructure are needed to optimize the use of the SID.